2017
DOI: 10.5391/ijfis.2017.17.3.170
|View full text |Cite
|
Sign up to set email alerts
|

Fingerprint Pattern Classification Using Convolution Neural Network

Abstract: Biometrics technology determines the correct identity of a person by extracting human biological or behavioral characteristic data. As the possibility of hacking increases with the development of IT technology, interest in biometrics and authentication technology is greatly increasing. Currently, the most popular authentication technology is fingerprint recognition. For the sake of efficiency, fingerprint recognition is divided into two stages. In the first step, the inputted fingerprint image is subjected to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 5 publications
0
21
0
2
Order By: Relevance
“…This training mechanism for convolution filters has made significant performance improvements in pattern recognition tasks such as image classification, character recognition, semantic segmentation, engineering classification, and so on. [2][3][4] RNNs are models that use both their current state and current input to determine its next state. 5 Traditional RNNs suffer from both vanishing gradient problem and exploding gradient problem.…”
Section: Deep Neural Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…This training mechanism for convolution filters has made significant performance improvements in pattern recognition tasks such as image classification, character recognition, semantic segmentation, engineering classification, and so on. [2][3][4] RNNs are models that use both their current state and current input to determine its next state. 5 Traditional RNNs suffer from both vanishing gradient problem and exploding gradient problem.…”
Section: Deep Neural Networkmentioning
confidence: 99%
“…To help model development, some graphical user interface (GUI)-based tools have been developed with which developers can construct a deep neural network model in a drag-and-drop manner. 4 It is convenient to use such tools when the number of layers is small enough to be drawn on the display window. However, they cannot handle large models on a small display window; hence, they are only appropriate for designing deep learning models with a relatively small number of layers.…”
mentioning
confidence: 99%
“…There are many application of CNN like image recognition, object detection, face recognition, fingerprint pattern classification etc. [12]. A standard CNN architecture consists of a combination of convolution layers (feed-forward layers) and pooling layers and after the last pooling layer, the network is connected to a fully connected layer.…”
Section: Introductionmentioning
confidence: 99%
“…Shrein [3] used Convolutional Neural Networks (CNNs) model for the fingerprint image classification and showed that effective image preprocessing can greatly reduce the dimensionality of the problem. Jeon and Rhee [4] also proposed the use of a CNN model combined with an ensemble model and a batch normalization technique after improving the quality of fingerprint images. Perrier [5] reported that Google announced the release of Tensorflow.js, a Javascript implementation of Tensorflow.…”
Section: Introductionmentioning
confidence: 99%